(3GdegPH aj GNJUGQ GdSff GdcHjQs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s; (3GdHjgbj , CHh HcQ CMeO Hf GdMSjf Hf Ydj GdHjgbj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s
(3ChdgG (B:s
(3bGd GdEeGe CHh HcQ CMeO Hf GdMSjf GdHjgbi GdMeO ddg HeG gh Cgdg hceG jfHZi dg s
(3BNQgG (B:s
(3jfJgi CKfGA GdcdGe Ydi CMGOjK Gdfgi Yf GdUdGI EPG GfJUa GdfgGQ MJi Jejd GdTeS hCNQ GdehLhO efg bhdg dbO cHQJ Sfi hQb YXei hGbJQH CLdi heGHi MGLI Cf CcPH Ydi Gddg (B" s
(3ajg CHhGH GdWgGQI hGdMjV hef GdUdGI Edi GdChbGJ GdecQhgI ai UaMI GdYfhGf HjGf hJhVjM defgL GdeDda HNWgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B206s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI (B731s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs